2016
DOI: 10.1021/acs.jafc.6b02255
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant-Activity Evaluation of Gallic-Acid-Grafted Chitosan Conjugate Synthesized by Free-Radical-Induced Grafting Method

Abstract: The major objective of this work was to develop a green and facile process to prepare gallic acid-chitosan conjugate and comprehensively evaluate the physicochemical properties and biological activities of an as-prepared water-soluble chitosan derivative. A free-radical-induced grafting approach using an ascorbic acid-hydrogen peroxide redox pair was adopted. The obtained conjugate was characterized by Fourier transform infrared spectroscopy, UV-vis, X-ray diffraction, and pKa analysis. The antioxidant activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(84 citation statements)
references
References 42 publications
9
73
1
1
Order By: Relevance
“…The results of this study show, that with the appropriate parameters, such as certain mass ratio between syringic acid and COSs (0.5:1), pH 5, temperature (27 o C), time (6 hours), the obtained derivative has syringic content, equal to 204 mg/g, corresponding to the level of grafting equal to 32%. The results of this study are similar to previous study, if mass ratio of gallic acid to chitosan is 0.5:1 24 . The enhancement of grafting degree was possibly due to the increasing of SA mass ratio within the critical range.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study show, that with the appropriate parameters, such as certain mass ratio between syringic acid and COSs (0.5:1), pH 5, temperature (27 o C), time (6 hours), the obtained derivative has syringic content, equal to 204 mg/g, corresponding to the level of grafting equal to 32%. The results of this study are similar to previous study, if mass ratio of gallic acid to chitosan is 0.5:1 24 . The enhancement of grafting degree was possibly due to the increasing of SA mass ratio within the critical range.…”
Section: Discussionsupporting
confidence: 91%
“…The COSs did not yield an absorbance peak in the range from 200 to 400 nm, whereas SA-COSs had two absorbance peaks at 210 and 261 nm. This pattern is identical to the characteristic absorbance peak o f SA, which should be assigned to the π-system of the benzene ring 24 , The results indicate, that SA was successfully grafted onto COSs. In the FT-IR spectra, SA-COS shows absorbance significant peaks in 1732 and 1632 cm −1 , implying both ester and amide stretching, respectively 25 .…”
Section: Characterization Of Sa-g-cosssupporting
confidence: 70%
“…For the synthesis of conjugates between phenolic acids and chitosan, the free radical reaction is often initiated by the H 2 O 2 /VC system [45,[54][55][56][57][58]. This system has several advantages.…”
Section: Free Radical-induced Conjugationmentioning
confidence: 99%
“…Since the degree of substitution (DS) of the conjugate is a key factor affecting its activity, many recent studies have focused on increasing the DS by optimizing the reaction conditions [54,55,57,58,63]. Some studies have shown that by increasing the ratio of polyphenols to chitosan in the critical range, the polyphenol content in the conjugate can be increased.…”
Section: Free Radical-induced Conjugationmentioning
confidence: 99%
“…However, the low water solubility of the pure chitosan at physiological pH has limited its application for the use of biomaterial fabrication. [9][10][11] In recent years several of its water-soluble derivatives have been prepared, such as quaternized and pegylated, 12 arginine grafted, 11 catechol group grafted, 10 gallic acid grafted 13 and carboxymethyl chitosan 14,15 derivatives are among some of the listed one. In all of these derivatives the incorporated moieties could have a plasticizing effect on the main polymer backbone, thus shielding the inter and intra-molecular interactions that could be evidenced from the reduced decomposition and lowered glass transition temperature (T g ).…”
Section: Introductionmentioning
confidence: 99%